From tourism to multilocal residence? - Marianna Elmi; Manfred Perlik (Revue de Géographie Alpine)
The article analyses the recent status and development of permanent inhabitants and second homes in the UNESCO World Heritage (WH) Dolomites area in the Italian Alps. First, the results show that a growth of permanent population is ongoing selectively in the urban and periurban areas, confirming earlier research in the Alpine arc and showing that agglomeration advantages are taking place. Second, the results show that these processes are parallel to a shifting use of second homes, announcing a transformation from an export-based to a residential economy in which second homes seem not to be homogeneously complementary to the tourist sector. Third, the Dolomites are not a homogenous region: despite the joint application process for WH site involving five provinces, demographic and economic differences can be highlighted along the provincial borders. This proves that demographic development is strongly path- dependent and conditioned by institutional settings and legislation. Therefore, ongoing strong agglomeration advantages and institutional differences are more decisive for the economic and demographic transformation in the Alps than single strategies carried out by local tourism consortia or enterprises. This brings to a relativization of the emerging debate about new migrants: regions with stable economic structures profit by gaining permanent residents, while regions with declining structures up to now attract mainly multilocal residents.